The Role of Inspirational Leadership in Succession Planning - An Analytical Study in the First Rusafa Education/Baghdad - Shaker Mahmoud, Mahmoud; Mohammed Yaseen Raheem, Mohammed Yaseen Raheem (Journal of Economics and Administrative Sciences, 2025)
This paper investigates the effect of motivation leadership on the performance of succession planning in the Ministry of Education / the First Rusafa Education/ Baghdad. The data was collected for the employees, which was analyzed using the inspirational leadership model. Other dimensions like creating inspiration for followers, future vision, communication, teamwork and mutual trust are also emphasized. The study shows that in order to realize optimal results, there needs to be constant support and supervision from the management. There were problems that were traced in the internal communication that led to this phenomenon. The role of an inspiring leader who is able to utilize the cognitive and behavioral capabilities of an individual to achieve the desired goal of the organization is very important. The research also points out that there is a great need for effective succession planning which aimed at nurturing and retaining talent within the organization. This accomplishment, together with the trained staff who are capable of making decisions that will take into consideration all the cognitive and behavioral capabilities that the organization can offer. This blended approach looks at improving overall performance and reaching organizational goals in the long term.